STUDI ANALISIS EFISIENSI ENERGI DAN TEKNO EKONOMI PENGERINGAN BUTIRAN MULTI TAHAP - J. P Sitompul; S Sumardiono; M. W Sariyanto (Mesin, 2001)
This paper concerns on analysis of energy in drying operation, because energy is crucial and determines process efficiency throughout. Further, techno-economy is also studied for drying agricultural product, such as paddy, in a multi-stage deep-bed dryer with focussing in study two-stage one. Thermal and drying efficiency have been evaluated from experiment data. Moreover, the techno-economy in view of energy consumption for drying operation is also considered . The analysis shows that the increasing of bed height for constant drying air temperature will significantly increase thermal and drying efficiency as well as energy consumption for dryer operation. Further, thermal efficiency, drying efficiency and energy consumption decreases with increasing the inlet drying air temperature which in turn reducing of drying cost operation. The study shows that the two-stage deep-bed dryer have higher thermal and drying efficiency and lower energy consumption compared to one-stage dryer.